International comparative analysis for enterprise resource management on the developing wine market of China - Sümegi, Zs.; Molnár, A. (International Journal of Horticultural Science, 2009)
However grape cultivation has long tradition in China, modem grape wine and wine production has only started 10 years ago, parallel with the Chinese economic boom, in 1998. The rise of the social welfare caused a higher demand for luxury products, wine drinking came more popular, since on the one hand it is representing the standard of western style living for the higher society class, on the other hand Chinese people can live a more healthy life and spend money on wine drinking, instead of drinking traditional spirits. This tendency opened a wide market for Chinese and international grape producers and winemakers. During our research we have collected the rare, available market information on the Chinese wine market. With the use of this statistical data we will analyse the collected information and rough out the future trends and opportunities and threads for trade companies on the emerging wine market.